2007
DOI: 10.1016/j.euromechsol.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Contact analysis of a flexible bladed-rotor

Abstract: This paper presents a model of fully flexible bladed rotor developed in the rotating frame. An energetic method is used to obtain the matrix equations of the dynamic behaviour of the system. The gyroscopic effects as well as the spin softening effects and the centrifugal stiffening effects, taken into account through a pre-stressed potential, are included in the model. In the rotating frame, the eigenvalues' imaginary parts of the latter matrix equation give the Campbell diagram of the system and its stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…1(f). This rather complicated behavior is difficult to predict and even to interpret as it was reported in the studies of numerous mechanical systems, see, e.g, [20,21,24,25,27,29,35,36,39,43,48]. The present work reveals that the untwisting of the Campbell diagrams is determined by a limited number of singular eigenvalue surfaces.…”
Section: Introductionmentioning
confidence: 78%
“…1(f). This rather complicated behavior is difficult to predict and even to interpret as it was reported in the studies of numerous mechanical systems, see, e.g, [20,21,24,25,27,29,35,36,39,43,48]. The present work reveals that the untwisting of the Campbell diagrams is determined by a limited number of singular eigenvalue surfaces.…”
Section: Introductionmentioning
confidence: 78%
“…Genta [6] indicated that the vibration of blade may cause the instability of the bladed rotor system. Lesaffre et al [7] investigated the contact problem of the rotating blade against the stationary outer case in the bladed rotor system. They discussed the frictionless sliding contact between the blades and the casing, without rubbing, and highlighted an unstable phenomenon near the stator critical speed.…”
Section: Introductionmentioning
confidence: 99%
“…In the role of oil film force, the system will show oil film instability phenomenon [21][22][23][24][25]. To clearly observe the dynamics characteristic of rotor system under the oil film force, then specially draw the threedimensional spectrum on the right neck (node 25) of the rotor system without fault, shown in Figure 5.…”
Section: The Influence Of the Oil Film Force On The Dynamicsmentioning
confidence: 99%